2008
DOI: 10.1074/jbc.m801291200
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 Inhibits Bax Activation and Apoptosis via a Phosphatidylinositol 3-Kinase-dependent Mechanism

Abstract: Hsp27 inhibits mitochondrial injury and apoptosis in both normal and cancer cells by an unknown mechanism. To test the hypothesis that Hsp27 decreases apoptosis by inhibiting Bax, Hsp27 expression was manipulated in renal epithelial cells before transient metabolic stress, an insult that activates Bax, induces mitochondrial injury, and causes apoptosis. Compared with control, enhanced Hsp27 expression inhibited conformational Bax activation, oligomerization, and translocation to mitochondria, reduced the leaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
160
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(173 citation statements)
references
References 46 publications
11
160
1
1
Order By: Relevance
“…58 In renal tubular cells, HSPB1 overexpression inhibited apoptosis and HSPB1 knockdown promoted apoptosis in response to culture in glucose-free medium containing sodium cyanide and 2-deoxy-D-glucose. 51 However, this kind of metabolic stress is of dubious clinical significance in the particular setting of DN. We now show that glomerular HSPB1 is upregulated in humans and in rats with short-(6 weeks) and long-standing (7 months) DN and that podocytes are the key sources of glomerular HSPB1 in both clinical and experimental DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 In renal tubular cells, HSPB1 overexpression inhibited apoptosis and HSPB1 knockdown promoted apoptosis in response to culture in glucose-free medium containing sodium cyanide and 2-deoxy-D-glucose. 51 However, this kind of metabolic stress is of dubious clinical significance in the particular setting of DN. We now show that glomerular HSPB1 is upregulated in humans and in rats with short-(6 weeks) and long-standing (7 months) DN and that podocytes are the key sources of glomerular HSPB1 in both clinical and experimental DN.…”
Section: Discussionmentioning
confidence: 99%
“…However, HSPB1 target molecules differ for different lethal stimuli and cell types. 50,51 In certain cells HSPB1 binds to cytochrome c released from the mitochondria and HSPB1 overerexpression prevents cytochrome-cmediated interaction of Apaf-1 with procaspase-9 and procaspase-9 activation. 28,30 In this regard, in human podocytes we observed that HSPB1 targeting promoted caspase-9 and HSP27 and podocytes MD Sanchez-Niñ o et al caspase-3 activity in the presence of Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…Although ABT-737 was able to cause in EGI-1 cells a marked increase of sensitivity to apoptosis mediated by ZOL, this increment, in TFK1 cells, was less pronounced. In short, ZOL treatment could behave as "priming" agent [37] which induces S-phase arrest, an insufficient pro-apoptotic signal, while ABT-737 by blocking BCL-2 and BCL-XL action lowers the threshold at which apoptosis may occur. The ZOL or ABT-737-induced apoptosis resistance, observed in cholangiocarcinoma cells when used as single agent prompted us to speculate the plausible involvement of HSP72-dependent PARP-1 inactivation and/or an HSP27-mediated BAX inactivation that may contribute to explain the increased cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…A potential additional mechanism that may contribute to increase the apoptosis resistance in TFK-1 cells is represented by the constitutive expression of pro-survival HSP27 [21,39,40]. This protein antagonizes BAX-mediated mitochondrial injury by inhibiting conformational activation of BAX thus reducing cytochrome c and AIF leakage and increasing significantly cell survival [37,41]. The resistance of EGI-1 and TFK-1 cholangiocarcinoma cell lines exposed to ABT-737 is multifactorial and could be ascribed to the presence of high levels of MCL-1 prosurvival protein (TFK-1), low level of BCL-2 (TFK-1), overexpression of HSP72 (TFK-1, EGI-1) or HSP27 (TFK-1).…”
Section: Discussionmentioning
confidence: 99%
“…By regulating the metabolism of glutathione (a major intracellular antioxidant) through the activation of glucose-6-phosphate dehydrogenase, Hsp27 protects cells from oxidative stress. Hsp27 can inhibit apoptosis through direct interaction with cytochrome c and inhibition of caspase activation and is also involved in the regulation of the Akt serine/threonine protein kinase pathway involved in cell survival (Aloy et al 2008;Havasi et al 2008). Because the overexpression of Hsp27 is frequently associated with thermotolerance and chemoresistance (Takhashi et al 2008;Li et al 1995), it appears to be a good candidate for explaining resistance to HIPEC.…”
Section: Discussionmentioning
confidence: 99%